The Effect of Community-Based Physiotherapy Programs on Chronic Disease Management in Rural Settings: A Systematic Review. - Oshomoji, Olawale Isreal; Ajiroba, Johnson Olasunkanmi (Journal of Advances in Medical & Biomedical Research)
Background & Objective: This systematic review evaluates the impact of community-based physiotherapy programs on the management of chronic diseases in rural areas. The study included 11 articles examining various chronic conditions, including diabetes, hypertension, chronic obstructive pulmonary disease (COPD), and persistent low back pain. The evidence indicates that these programs substantially improve health outcomes, reduce healthcare utilization, and are cost-effective. Materials & Methods: The review analyzed data from 11 articles focused on managing chronic diseases through community-based physiotherapy programs. It assessed their effectiveness in rural populations across conditions such as diabetes, hypertension, COPD, and persistent low back pain. The review adhered to PRISMA guidelines for conducting and reporting systematic reviews. Results: The findings suggest that community-based physiotherapy programs significantly improve health outcomes, decrease healthcare utilization, and are economically viable. However, barriers such as a shortage of physiotherapists, financial constraints, and cultural differences limit widespread implementation. The potential role of telehealth in expanding the reach of these services was also highlighted, although challenges related to internet access and digital literacy persist. Conclusion: Future research should aim to address these barriers, explore long-term effects, and develop culturally tailored interventions to enhance the effectiveness of physiotherapy programs in rural settings. Policy recommendations include increasing financial support, facilitating the recruitment of physiotherapists, and integrating telehealth into rural healthcare delivery systems.